2014
DOI: 10.1021/ja510435u
|View full text |Cite
|
Sign up to set email alerts
|

Aspartame-Stabilized Gold–Silver Bimetallic Biocompatible Nanostructures with Plasmonic Photothermal Properties, Antibacterial Activity, and Long-Term Stability

Abstract: Gold–silver core–shell nanoparticles stabilized with a common sweetener, aspartame (AuNP@Ag@Asm), combine the antimicrobial properties of silver with the photoinduced plasmon-mediated photothermal effects of gold. The particles were tested with several bacterial strains, while biocompatibility was verified with human dermal fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(91 citation statements)
references
References 23 publications
4
85
0
Order By: Relevance
“…[25][26][27][28] Au NPs have advantages of easy preparation, homogeneity and biocompatibility, but suffer from low antibacterial property. Madhuchanda Banerjee et al 29 fabricated bimetallic Au@Ag NPs with positive charges on the surface.…”
Section: -14mentioning
confidence: 99%
“…[25][26][27][28] Au NPs have advantages of easy preparation, homogeneity and biocompatibility, but suffer from low antibacterial property. Madhuchanda Banerjee et al 29 fabricated bimetallic Au@Ag NPs with positive charges on the surface.…”
Section: -14mentioning
confidence: 99%
“…Fasciani et al have reported that the benzoyl radicals (BRs) under the air conditions are transferred to benzoyl-type acids (BAs). [22] Under the present reaction conditions (with traces of oxygen) the abrupt increase in the initial rate of polymerization might be somehow connected with the formation of peroxides via the excited benzoyl fragments and oxygen. Table 1 shows the weight, viscosity and number average molecular weights and the molecular weight distribution as a function of AAm concentration.…”
Section: Methodsmentioning
confidence: 69%
“…Photolysis and initiating radical formation: Darocur (Dar), ketyl radical (Kr), benzoyl radical (Br). [22] However, the abrupt decrease in the polymerization rate with conversion at the very low conversion range indicates that the k p /k t s are not able to explain this behavior. Thus, we should include other parameters such as the photoinitiator efficiency, average or local monomer comcentration and impurities.…”
Section: Methodsmentioning
confidence: 99%
“…33 Broth microdilution antibacterial assay was used to determine minimum inhibitory concentrations. The experiment was performed on strains of S. aureus subsp.…”
Section: Core-shell Gold-silver Nanoparticlesmentioning
confidence: 99%
“…Biocompatibility testing was performed using the MTS cell proliferation colorimetric assay, in which any significant effect on the proliferation of primary dermal fibroblasts following treatment with AuNP@Ag@Asm at different concentrations was not observed. 33 …”
Section: Core-shell Gold-silver Nanoparticlesmentioning
confidence: 99%